TINGKAT KEPARAHAN GEJALA MENOPAUSE DAN TINGKAT KECEMASAN PADA WANITA MENOPAUSE - Engelina Totoda, Serlince (JPK : Jurnal Penelitian Kesehatan, 2023)
Menopause is a condition where there is a change in hormon levels that cause physical changes and psychological changes that affect the psychological condition of menopausal women in the form of anxiety. This phenomenon is found in RW X Kelurahan Tanah Kali Kedinding Surabaya where menopausal PKK mothers feel anxious because of the changes that occur. The aim of the study was to analyze the relationship between the severity of menopausal symptoms and the level of anxiety in menopausal women. The research design is a correlation study with the CrossSectional approach. The research respondents were 56 menopausal PKK mothers in RW X, Tanah Kali Kedinding Surabaya who met the inclusion criteria and used simple random sampling technique. The severity of menopausal symptoms as an independent variable was measured by the MRS (Menopause Rating Scale) questionnaire and anxiety level in menopausal women as the dependent variable measured by the TMAS (Taylor Manifest Anxiety Scale) questionnaire. The results showed 46.4% of respondents experienced the severity of mild menopausal symptoms and more than 50% (66.1%) of respondents experienced moderate anxiety. Rank Spearman test results using SPSS 23 for Windows, p = 0,000 (? = 0.05) where p<? means H1 is accepted with correlation coefficient +0.570, there is a moderate positive relationship between the severity of menopausal symptoms and anxiety levels in menopausal women at RW X District of Tanah Kali Kedinding Surabaya, which means the more severe the severity of menopausal symptoms, the more severe anxiety of menopausal women. Suggestion for the head of RW X to collaborated with the Puskesmas Tanah Kali Kedinding Surabaya in improving education about healthy lifestyle and importance of husband’s support to reduce anxiety, especially the sexual aspect of marriage